Exploring the Antimalarial Efficacy of Globimetula oreophila Leaf Fractions in Plasmodium berghei-Infected Mice: In Vivo Approach - Garba, Dauda; Ali, Bila Hassan; Bawa, Bashar; Sanusi, Abdulrazaq; Sani, Yahaya Mohammed; Magaji, Muhammad Garba; Abdullahi, Musa Isma’il; Musa, Aliyu Muhammad; Sadiya, Hassan Halimatu (Sciences of Phytochemistry, 2024)
The development of parasite resistance to first-line antimalarial medicines, especially the Artemisinin-based combination therapies (ACTs), has made the research and development of novel antimalarial medications vital. Globimetula oreophila, a plant used in traditional medicine to treat malaria, is a natural product that may provide new antimalarial drugs with fewer side effects, greater efficacy and lower risk of resistance than synthetic drugs. This study aims to evaluate the antiplasmodial properties of G. oreophila's fractions. The plant leaves were air-dried and reduced in size using a pestle and mortar. The pulverized plant was macerated in 70% ethanol and fractionated with solvent in increasing polarity of n-hexane, chloroform, ethyl acetate, and n-butanol to produce the various fractions. The antiplasmodial activity of the n-hexane, chloroform, ethyl acetate, and n-butanol fractions of G. oreophila leaf extract was assessed using an in vivo method in Plasmodium berghei-infected mice via prophylactic, suppressive, and curative test. The fractions' median lethal dose (LD50) was estimated to be greater than 5000 mg/kg in mice. The median effective dose (ED50) of the fractions at doses of 125, 250, and 500 mg/kg produced a significant (p<0.001) decrease in the level of parasitemia. The ethyl acetate fraction had the best antiplasmodium activity compared to other plant fractions. The fractions of G. oreophila showed significant in vivo antiplasmodial activity, which upholds the earlier in vivo findings for the crude extract and its folkloric use. Further study should be carried out to isolate active secondary metabolites responsible for this observed antimalarial activity in all four investigated fractions.